In vitro activity of tigecycline against 2423 clinical isolates and comparison of the available interpretation breakpoints. - Papaparaskevas, Joseph; Tzouvelekis, Leonidas S; Tsakris, Athanassios; Pittaras, Theodore E; Legakis, Nicholas J (Diagn Microbiol Infect Dis, 2010)
MICs to tigecycline and 12 antimicrobials were performed by microdilution method, against 2423 nonduplicate pathogens recently isolated in 17 Greek hospitals. The Food and Drug Administration (FDA) and European Committee on Antimicrobial Susceptibility Testing (EUCAST) criteria were used comparatively for interpretation of tigecycline MICs. Tigecycline exhibited potent in vitro activity against the majority of the isolates tested. (MIC(90) values of 0.5, 1, 2, 0.125, 1, 0.25, 0.125, and 1 mg/L were observed for Escherichia coli, Klebsiella pneumoniae, Enterobacter spp., Moraxella catarrhalis, Acinetobacter spp., Staphylococcus aureus, Enterococcus spp., and Streptococcus pneumoniae isolates, respectively.) Tigecycline activity was the same, irrespective of the resistance profile to other antimicrobials (Gram-negative pathogens susceptible or resistant to imipenem, Enterococcus spp., S. aureus, or S. pneumoniae isolates, susceptible or resistant to vancomycin, methicillin or penicillin, respectively). Interpretation using EUCAST and FDA breakpoints differed among isolates of K. pneumoniae and Enterobacter spp. having tigecycline MICs of 2 to 4 mg/L. In conclusion, tigecycline exhibited potent activity against pathogens recently isolated in a region that experiences high antimicrobial resistance rates. Indications that the available criteria might categorize differently tigecycline susceptibility status in K. pneumoniae and Enterobacter spp. isolates were also detected.
Keywords: Anti-Bacterial Agents; Bacterial Infections; Drug Resistance, Bacterial; Gram-Negative Bacteria; Gram-Positive Bacteria; Greece; Humans; Microbial Sensitivity Tests; Minocycline